PENGARUH KOMPRES HANGAT REBUSAN JAHE TERHADAP PENURUNAN INTENSITAS NYERI SENDI LUTUT PADA LANSIA YANG MENGALAMI OSTEOATHRITIS DI PUSKESMAS KUTARAYA - Yora Nopriani; Bela Purnama Dewi; Ani Siska (LPPM STIKes Mitra Adiguna, 2024)
Aging or getting old is a condition that occurs in human life. The process of aging is a lifelong process, not only starting at the beginning of life. Along with the aging process, the body will experience various health problems. One of them is osteoarthritis which is a bone and joint disease that occurs as a result of the aging process. The purpose of this study was to study the effect of warm water compress therapy on reducing osteoarthritis joint pain in the elderly at the Kutaraya Health Center. This type of research uses quantitative research methods with the type of pre-experimental research. The design used in this study was a pre-post test design, with a one group pretest and post test design. where the population is 52 people and the sample is 24 people with the characteristics of the elderly who experience joint pain osteoarthritis. The sampling technique used is Type Probability sampling, namely Simple Random Sampling. Data collection methods used were interviews and questionnaires. Presentation of characteristic distribution table data with the Wilcoxon test statistic. The results showed that more than half experienced osteoarthritis joint pain with a moderate pain scale of 10 elderly people (80%). Based on the results of statistical tests using the Wilcoxon test, it was found that ? value = 0.000, with a value of ? = 0.05 (? <?), this means that there is an effect of warm compresses with ginger on knee joint pain in the elderly who have Osteoathritis at the Kutaraya Health Center, Kayu Agung City. 2023. The conclusion is that ginger warm compresses have an effect on the level of knee joint pain in the elderly who have osteoarthritis.